EVALUASI EFEKTIFVITAS PENGELOLAAN SUMBER DAYA MANUSIA DALAM PENGEMBANGAN ORGANISASI DI POLITEKNIK MFH - Syahrul, Syahrul (Journal of Innovation Research and Knowledge, 2025)
This study aims to evaluate the effectiveness of human resource (HR) management in organizational development at MFH Polytechnic. Effective HR management plays an important role in improving organizational performance, especially in the context of higher education that continues to grow. This study uses a quantitative approach with a descriptive analytical method, where data is collected through surveys, interviews, and documentation related to HR management at the MFH campus. The population in this study involved all teaching staff and education personnel at Medika Farma Husada Mataram Polytechnic, with samples taken purposively. The instrument used in this study was a questionnaire consisting of various indicators related to HR management, such as recruitment, training, career development, and performance evaluation. The collected data were analyzed using descriptive statistical analysis techniques to provide an overview of the effectiveness of HR management in supporting organizational development. The results of the study indicate that HR management at MFH Polytechnic has generally been running well, but there are still several areas that need to be improved, such as the implementation of more structured training and career development programs, as well as more objective and sustainable performance evaluations. In addition, communication factors between parts of the organization are also considered necessary to support more optimal development